Religion and Economics : From the Transformation of the Human Capital Index (HCI) to the Economic Sovereignty of Islamic Boarding Schools in Indonesia - Dede Aji; Rifki Rosyad (Yayasan Ahmar Cendekia Indonesia, 2020)
The purpose of this study is to analyze the role of the boarding school leadership in improving the quality of human resources as a whole. The contribution of human resources is very important in the progress of this boarding school. The method used is through a phenomenological approach, in which the researcher is directly involved in the struggle of society and the students directly. Researchers observe and analyze and interview the parties who are directly related. The success of building a nation, starting from the development of human resources, HCL (Human Capital Index) plays a very important role in the development of civilization towards SGDs. The HCL component, which includes education, health and social security, has been implemented in the Idrisyah Islamic boarding school, as a Tarekat. The application of the HCL principles greatly impacts on sustainable human development. Tarekat in Indonesia that apply it because they still apply spirituality of worship vertically, the majority do not have an impact on socio-culture, economy, development and others and as a result unemployment, poverty is not significantly reduced. This tarekat is a new trend in socio-societal change and as a Sufistic movement in Indonesia.